Some Morpho-Biological Characteristics Of А. Albidium And А.Tenifolium Populations - Ergashali Ruzmatov; Oygul Shirinova (Zien Journals, 2023)
This article provides information on the signs of adaptation to environmental conditions in the formation of leaves of the plant species Acanthophyllum albidum Schischk, A. tenuifolium Schischk
Keywords: plant; ontogeny; saponin; environment